Resilience of refugee families - Batić Dragana (Temida)
This study attempted to find a correlation between the trauma of family members of war and exile, and the characteristics of family functioning and lasted from 1992-1995. The term “family resilience” refers to the processes of adaptation and coping in the family as a functional unit. This paper presents a study of refugee families from Bosnia, who lived in refugee camps in Macedonia during the war of 1992- 1995. Data were obtained by interviews, observations, and a number of psychological instruments especially for children and parents, which measured the effects of psychological stress and family relationships. Based on the results obtained by quantitative and qualitative analysis, and application of theoretical models of systemic theory and family therapy, existence for four types of refugee families has been found and described, depending on the structure and the level of functionality.